The Effect of Balcony to Enhance Natural Ventilation in Local Houses in Mazandaran Province - Rood Posht, Azadeh Mahmoudi Kohneh; Daneshjoo, Khosro; Shemirani, Seyed Majid Mofidi (Journal of History Culture and Art Research, 2017)
Utilization of natural ventilation in buildings has a long history. Architecture has been trying to response to weather conditions all the time. Wind catcher, mashrabiya, portico and iwan are some examples of climate designs in vernacular architecture which have shown the importance of natural ventilation since a long time ago. The efficiency scope of natural ventilation when used with other cooling techniques will be more widespread. Today, designing desirable buildings using natural ventilation requires knowing theoretical foundations and a detailed study based on new knowledge regarding the feasibility of the use of components design and equipment related to natural ventilation. The present research aims to offer architects some design solutions in order to take advantage of natural ventilation in buildings using the vernacular architecture. Through matching features of functional spaces in local houses with climatic characteristics of regions around the Caspian sea (Mazandaran province) and determining the pattern used in these spaces in housing areas, the present study seeks to answer this question: “Are types of local houses in regions with moderate and humid climate in Iran (Mazandaran) consistent with regional climate in terms of patterns applied in internal functional spaces? How do regional climate features affect physical form of houses?” The results show that there is a direct and consistent relationship between vernacular architectural features of Mazandaran province and climate classification and regional climate. It also enhances home comfort in summer and finally, it can be concluded that local houses are built based on the climate classification and environment context, and natural ventilation is the most important factor affecting the conditions which improve environmental comfort. The present research provides some guidelines for the architectural design of residential buildings in regions with moderate and humid climate with the aim of achieving maximum level of natural ventilation. Also, in order to exploit the potential of natural ventilation, the results of the research will help architect select optimal designing parameters in harmony with the regional climate.